Ensuring Access to Various Social Services for Children with Special Needs and Their Families After Disasters - Aslan, Harun (Nobel Tip Kitabevleri, 2024)
This study examines in depth the impacts of disasters on children with special needs and their families and their needs to access social services. The research addresses in detail the biopsychosocial challenges faced by these vulnerable groups and offers strategies on how these needs can be met in post-disaster responses. The chapter discusses basic needs and support services for individuals with special needs, as well as barriers to access and how these barriers can be overcome. It also focuses on how disaster management systems can better meet the needs of these groups through policy and practice recommendations. As a result, the importance of multidisciplinary approaches and community-based interventions are emphasized, and recommendations are developed to contribute to the post-disaster social integration and recovery processes of children with special needs and their families.